Use of Acetylcysteine as the Life-saving Antidote in Amanita phalloides (Death Cap) Poisoning - Montaninia, Salvatore; Sinardia, Daniele; Praticò, Caterina; Sinardia, Angelo Ugo; Trimarchi, Giuseppe (Arzneimittelforschung, 1999)
α-Amanitin is an amatoxin known to produce deleterious effects on the liver and the kidneys, when circulating in the blood. It is produced by a particular kind of mushroom called amanita phalloides. Therapeutic options employed to treat mushroom intoxication, such as haemodiaperfusion on activated charcoal, high dosages of penicillin G, oral charcoal, etc., very often failed to act properly and liver transplantation (when a graft is available) appeared to be the only solution. In recent years, as suggest by some authors, it has been postulated that the oxidant effects of α-amanitin could be counteracted by the use of antioxidants such as silibinin. High dosages of N-acetyl-cysteine (CAS 616-91-1, NAC), already used as antioxidant in paracetamol poisoning, were successfully used in our Intensive Care Unit (ICU) in the treatment of Amanita phalloides poisoning.In the last two years, 11 patients (mean age of 5−72 = 38.5) were treated for Amanita phalloides poisoning of various degrees, with a protocol (haemodiaperfusion on activated charcoal, high dosages of penicillin G, etc.) further comprehending NAC (fluimucil®). All the patients recovered successfully but one (bearing precedent liver disease) needed liver transplantation. Daily monitoring of liver enzymes, creatinine, coagulation, LDH, blood and urinary α-amanitin were used to screen the progresses of the patients.
Keywords: N-Acetylcysteine; α-Amanitin; Antidote; CAS 616-91-1; Fluimucil®; clinical studies